2018
DOI: 10.1016/j.biombioe.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pilot-scale pyro-gasification and activation conditions on porosity development in activated biochars

Abstract: Few studies have examined the influence of pyro-gasification and activation conditions on porosity development in activated biochars. In this context, this study investigates the effects of pyrogasification temperature (315, 399, and 454 °C), activation temperature (700, 800, and 900 °C), and activating agent (CO2 flow rate: 2, 3, and 5 L min -1 ) on porosity in materials made from wood residues (black spruce and white birch). Activated biochars were prepared in a two-step process: torrefaction/fast pyrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 70 publications
(81 reference statements)
2
20
0
Order By: Relevance
“…The battery electrode material grade will substantially contain more value and so thus required energy to treat the waste at high temperatures (>1000°C). The application requiring posttreatment in terms of activation 58 and magnetic biochar composites 59 production will subsequently raise the price of the char. The effect of O/C, N/C, and chlorine content on the energy recovery was analysed by regression analysis (Figure 9).…”
Section: Economic Analysismentioning
confidence: 99%
“…The battery electrode material grade will substantially contain more value and so thus required energy to treat the waste at high temperatures (>1000°C). The application requiring posttreatment in terms of activation 58 and magnetic biochar composites 59 production will subsequently raise the price of the char. The effect of O/C, N/C, and chlorine content on the energy recovery was analysed by regression analysis (Figure 9).…”
Section: Economic Analysismentioning
confidence: 99%
“…The regression analysis indicated that pyrolysis temperature had no significant impact on the final surface area or pore volume. Similarly, the influence of torrefaction/fast pyrolysis of white birch and black spruce on the porosity development of CO2-activated biochars was statistically exanimated by Braghiroli et al [174]. The pyro-gasification temperature was varied from 588 to 727 K and the activation temperature varied from 973 to 1173 K. It was concluded that the first step pyro-gasification had less impact on the porosity of activated biochars while the activation temperature was the major variable to optimize their surface area.…”
Section: Effects Of Pyro-gasification Conditions On the Porosity Of Amentioning
confidence: 96%
“…The current challenge in activated biochar production is that only laboratory-scale furnaces have been tested to date. Braghiroli et al [174] produced highly porous physically and chemically activated biochars made from wood residues through a torrefaction/fast pyrolysis industrial furnace (Airex Energy, Canada, 250 kg h -1 ) and a prototype activation furnace (slow pyrolysis in a shaftless screw conveyor reactor, 1 kg h -1 ). One promising direction would be to combine both furnaces having flexible and scalable activation processes with high temperatures (up to 1173 K) and long residence times (1 h minimum) at various heating rates.…”
Section: Reactor Designmentioning
confidence: 99%
“…The torrefaction/fast pyrolysis plant converted wood particles into torrefied wood (315 • C) and biochar (400 and 455 • C) in an oxygen-free environment. More details on biochar preparation have been described elsewhere [22].…”
Section: Materials Sampling and Biochar Preparationmentioning
confidence: 99%